Change in Self-Criticism Across Emerging Adulthood and Psychological Well-Being at Age 35: The Mediating Role of Reflectivity. Issue 2 (April 2022) - Michaeli, Yossi; Dickson, Daniel J.; Hakhmigari, Maor Kalfon; Scharf, Miri; Shulman, Shmuel
Recent conceptualization and research in personality development have shown that significant changes in personality taking place during emerging adulthood where young people tend to become more emotionally mature and stable. In line with these contentions, we examined in a sample of 205 Israeli emerging adults the longitudinal association between change in self-criticism across ages 23 and 29 and positive developmental and psychological well-being outcomes at age 35. In addition, we examined the extent to which the association between change in self-criticism and future outcomes would be mediated through reflectivity. Findings indicated that greater decrease in self-criticism during emerging adulthood associated with greater reflective capability at age 29 and both longitudinally associated with greater achievement of developmental tasks and better psychological well-being at age 35. Additionally, associations of decrease in self-criticism with future outcomes were mediated through reflectivity. These findings point to maturity processes that can explain outcomes in young adulthood.